Non-coding RNA LINC00473 mediates decidualization of human endometrial stromal cells in response to cAMP signaling - Liang, Xiao-Huan (Sci Rep, 2016)
Decidualization is an essential step in the establishment of pregnancy. However, the functional contributions of long intergenic noncoding RNAs (LincRNAs) to decidualization have not been explored. To explore the regulation and role of LincRNAs during human decidualization, human endometrial stromal cells (HESCs) are induced to undergo in vitro decidualization by treating with estradiol-17β, db-cAMP and medroxyprogesterone acetate. LINC00473 (LINC473) expression is highly induced in HESCs after decidual stimulus. We found that cAMP-PKA pathway regulates the expression of LINC473 through IL-11-mediated STAT3 phosphorylation. RNA interference-mediated down-regulation of LINC473 inhibits in vitro decidualization. These results suggested that LINC473 might be functionally required for human decidualization. This is the first report demonstrating the presence of LincRNA during human decidualization.